2005
DOI: 10.1159/000088381
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Ability between a Fast Strategy, Tendency-Oriented Perimetry, and the Standard Bracketing Strategy

Abstract: Purpose: To compare the diagnostic abilities of the standard bracketing strategy (BR) and a fast strategy, the tendency-oriented perimetry (TOP). Methods: Seventy-seven controls and 91 eyes from patients with glaucoma were analyzed with the strategies TOP and BR. Sensitivity (Se), specificity (Sp), the area under the receiver operating characteristic (ROC) curve (AC) and the optimum cutoff value (CO) were calculated for the visual field indices mean defect (MD), the square root of the loss variance (sLV) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Los principales componentes de LV son la fluctuación del umbral, su irregularidad topográfica y los errores. Los errores se limitan en TOP al reducirse el «efecto fatiga» neurológico, las faltas de atención y los defectos metodológicos causados por examinar los puntos de forma independiente (27)(28)(29). Flammer (30) indicó que el primer signo de glaucoma no son los defectos focales o difusos sino el incremento de la fluctuación del umbral.…”
Section: Discusión Discusión De Los Resultados Funcionalesunclassified
“…Los principales componentes de LV son la fluctuación del umbral, su irregularidad topográfica y los errores. Los errores se limitan en TOP al reducirse el «efecto fatiga» neurológico, las faltas de atención y los defectos metodológicos causados por examinar los puntos de forma independiente (27)(28)(29). Flammer (30) indicó que el primer signo de glaucoma no son los defectos focales o difusos sino el incremento de la fluctuación del umbral.…”
Section: Discusión Discusión De Los Resultados Funcionalesunclassified
“…In the initial stages of glaucoma, retinal dysfunction manifests as alterations in the homogeneity of responses more than as the presence of evident defects. This has been shown in examinations using the TOP strategy with both conventional stimuli (1820) and Pulsar stimuli (2123).…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies we have indicated that BRA tends to produce excessively high sLV values in normal subjects, whereas in TOP this index has the best diagnostic capacity [18]. Filtering corrects this tendency in BRA and tends to equalize results of the two strategies in this regard.…”
Section: Discussionmentioning
confidence: 87%
“…It has been suggested that this procedure involves loss of spatial information [1,25]. However, in light of the results described using filtered threshold procedures, it seems that the short duration TOP procedure actually provides a more reliable threshold value since it reduces "fatigue effect" and simultaneously acts as an averaging filter of the area [17,18].…”
Section: Introductionmentioning
confidence: 99%